A first exploratory analysis of the regional economic impact of COVID-19 in Argentina - Niembro, Andrés (2020)
In this article, we present a first exploratory analysis of the regional economic impact that COVID-19 pandemic and lockdown measures adopted in Argentina could have had during the last weeks of March and the month of April, the period of greatest economic impact, when restrictions were mainly raised at the sectoral level, without taking into account any regional criteria. To this end, we built an index of territorial economic impact by COVID-19 (ITEI-COVID), which takes into account, on the one hand, the regional production structure in terms of formal private employment, and on the other hand, the operational level of each sector. Results show that the regional impact of COVID-19 on private economic activity in Argentina was highly heterogeneous and that these unequal effects were largely related to the degree of productive diversity or the type of regional specialization. All these results are relatively stable and robust when comparing different geographical units of analysis, when changing the period chosen to define the private production structure, or when considering the informality and self-employment in addition to formal salaried employment.